Review of Adaptation in Young Adult Novels: Critically Engaging Past and Present - Dainy Bernstein (International Journal of Young Adult Literature, 2021)
While a fair amount of scholarship exists on adaptation in children’s literature, discussion of adaptations in young adult literature has thus far been limited mostly to ideas of pedagogy, in considerations of how adaptations might be utilized in high-school classrooms to encourage interest in the canonical texts. The essays in Adaptation in Young Adult Novels: Critically Engaging Past and Present do consider this use, acknowledging that YA adaptations are often employed as an introduction to the source texts, but they go beyond pedagogical evaluation to analyze how adaptation works in a specifically adolescent context. Editors Dana E. Lawrence and Amy L. Montz identify the effect of adaptation as a means of “engaging with our predecessors and the rights—and wrongs—of their literatures” (2). Through critically engaging the past and the present as they commingle in young adult adaptations, Lawrence and Montz argue, these texts “empower young readers, making them more culturally, historically, and socially aware through the lens of literary diversity” (2).